Focus on translational research from arabidopsis to crop plants and beyond - Roeder, Adrienne H.K.; Argueso, Cristiana T.; Williams, Mary; Auge, Gabriela; Li, Xin; Strader, Lucia; Uauy, Cristobal; Wu, Shuang (Oxford University Press, 2025)
Over the past 4 decades, substantial research efforts in plant science worldwide have focused on the model system Arabidopsis thaliana (Provart et al. 2015). Many of us have dedicated years to the study of Arabidopsis, motivated by the notion that our findings will yield advancements in agriculture and natural ecosystems. Considering translation holistically as the gene functions, pathways, and technologies discovered and developed in Arabidopsis that inform our understanding of other plants, Arabidopsis has had a powerful influence. In particular, the annotation of plant genomes heavily relies on the gene functions elucidated in Arabidopsis (Whitt et al. 2020; Wimalanathan and Lawrence-Dill 2021; Fattel et al. 2022). Many technologies and techniques pioneered in Arabidopsis have been successfully translated to crops and other plant species (Yaschenko et al. 2025). Remarkably, discoveries in Arabidopsis and other plants have also contributed significantly to biomedical research (Jones et al. 2008; Strader et al. 2025). For example, the auxin degron system is widely used to degrade proteins on demand in animal/human cells by adding auxin to the cell cultures (Nishimura et al. 2009). Further, Arabidopsis research aimed at understanding plant adaptation to changing environments, with the goal of predicting evolutionary trajectories, holds the potential to guide conservation efforts in the face of climate change (Hancock et al. 2011; Assmann 2013; Wilczek et al. 2014; Arana and Picó 2025). However, we must ask the question of whether the features that make Arabidopsis a powerful model (i.e. its compact genome, ease of transformation, small size, and inexpensive growth) remain exclusive to this plant and whether the lessons learned from peculiar features of Arabidopsis can be extrapolated to plants we cultivate or those living in natural ecosystems, either directly or indirectly. Twenty-five years after the publication of the Arabidopsis genome sequence in 2000 (AGI 2000), it is a good time to reflect on the impact of research in Arabidopsis in this focus issue.